(untitled) (The Agriculturists, 2010)
Some chemical compositions of mango harvested at 24, 18, 12, 6 days before optimum maturity and at optimum maturity were analyzed. The amount of ascorbic acid, ?-carotene and sugars of the harvested mangoes were significantly influenced by the stages of harvest and period of storage. Amount of ascorbic acid of the harvested mango fruits was the highest just after harvest. It was sharply declined with the elapse of time in storage. Fruits harvested before optimum maturity showed the highest amount of ascorbic acid, which decreased in delay of harvest. ?-carotene was quite low at harvest but rapidly increased in storage. Fruits harvested before optimum maturity showed minimum ?-carotene and it rapidly increased in late harvested fruits. Total sugar, reducing sugar and non reducing sugar were sharply increased at optimum ripe stage, while slightly declined at last edible stage. All the sugars were the lowest at earliest harvests, which increased gradually with delay in harvest.